The last dress from Paris [large type] - Beer, Jade (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"London, 2017. There's no one Lucille adores more than her grandmother. So when her beloved Granny Sylvie asks for Lucille's assistance with a small matter, she's happy to help. The next thing she knows, Lucille is on a train to Paris, tasked with retrieving a priceless Dior dress. But not everything is as it seems, and what Lucille finds in a small Parisian apartment will have her scouring the city for answers to a question that could change her entire life. Paris, 1952. Postwar France is full of glamour and privilege, and Alice Ainsley is in the middle of it all. As the wife to the British ambassador to France, Alice's job is to see and be seen--even if that wasn't quite what she signed up for. Her husband showers her with jewels, banquets, and couture Dior dresses, but his affection has become distressingly elusive. As the strain on her marriage grows, Alice's only comfort is her bond with her trusted lady's maid, Marianne. But when a new face appears in her drawing room, Alice finds herself yearning to follow her heart...no matter the consequences. The City of Light comes alive in this lush, evocative tale that explores the ties that bind us together, the truths we hold that make us who we are, and the true meaning of what makes someone family"--